Penerapan Metode Rapid Aplication Development pada Pengembangan Sistem Informasi Manajemen Aset Studi Kasus Quality Parking - Mirza, Anis; Lusita, Melani Dewi (Jurnal Informatika Universitas Pamulang, 2021)
Quality Parking is the main part of the Quality Service Group which is totally committed to providing quality Quality Parking services for all users as the manager of goods parking services. Quality Parking provides products from product providers to purchase products and redistribute them to customers but information on availability of goods is not yet clear. Information on the availability of goods according to the data collection and reporting process is still inefficient. Recording activities take a long time even though the information is very much needed. The recording process can experience an error in the calculation of goods so that the resulting report is less accurate. The inventory system that is running provides a gap for errors made by the admin such as the improper recording process between the data and the physical stock of goods. Based on these problems, the researcher intends to create a goods information system using computer technology that can speed up the activities of recording incoming and outgoing stock of goods. The system developed can provide convenience in recording and making inventory reports quickly and accurately. Research that has been done to create an inventory information system using the PHP computer programming language with MySQL database.